(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
Abstract: The importance of working memory in language acquisition is examined in this article, with a focus on English as a Foreign Language (EFL) learners. Working memory facilitates vocabulary retention, grammar comprehension, and reading and listening comprehension. Strong working memory learners typically attain higher levels of language competency, according to research, whereas learners with weaker working memory may struggle with processing and retention. The article covers technology tools to improve working memory as well as instructional tactics for these learners, including chunking, visual aids, and spaced repetition. Improved language acquisition results for EFL learners can result from teaching strategies that prioritize working memory.